UDP-N-Acetylglucosamine Pyrophosphorylase 2 (UAP2) and 1 (UAP1) Perform Synergetic Functions for Leaf Survival in Rice - Wang, Zhaohai; Wang, Qiang; Wei, Lingxia; Shi, Yan; Li, Ting; Hu, KeKe; Liu, Shuai; Zhong, Hua; Liao, Jianglin; Li, Yangsheng; Zhang, Hongyu; Huang, Yingjin (Frontiers in Plant Science, 2021)
Functional inactivation of UDP-N-acetylglucosamine pyrophosphorylase 1 (UAP1) induces defense response-related lesion-mimic spots and subsequent early senescence in every newly grown leaf of the rice mutant uap1 after a short period's normal growth. However, the molecular mechanism of these leaves sustaining the short period's survival is still unknown. Phenotypic and molecular studies show that defense response-related lesion-mimic spots and early leaf senescence appear on the normally grown uap1 leaf and aggravate with the growth time. Bioinformatic analysis reveals that UAP proteins are evolutionarily conserved among eukaryotes, and there exists UAP2 protein except UAP1 protein in many higher organisms, including rice. Rice UAP2 and UAP1 proteins present high sequence identities and very similar predicted 3D structures. Transcriptional expression profile of the UAP2 gene decreases with the appearance and aggravating of leaf spots and early senescence of uap1, implying the role of the UAP2 gene in maintaining the initial normal growth of uap1 leaves. Enzymatic experiments verified that the UAP2 protein performs highly similar UAP enzymatic activity with the UAP1 protein, catalyzing the biosynthesis of UDP-GlcNAc. And these two UAP proteins are found to have the same subcellular localization in the cytoplasm, where they most presumably perform their functions. Overexpression of the UAP2 gene in uap1 plants succeeds to rescue their leaf mutant phenotype to normal, providing direct evidence for the similar function of the UAP2 gene as the UAP1 gene. The UAP2 gene is mainly expressed in the young leaf stage for functions, while the UAP1 gene is highly expressed during the whole leaf developmental stages. Based on these findings, it is suggested that UAP2 and UAP1 play key roles in rice leaf survival during its development in a synergetic manner, protecting the leaf from early senescence.